2007
DOI: 10.1007/s11419-007-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of cannabidiol to Δ9-tetrahydrocannabinol and related cannabinoids in artificial gastric juice, and their pharmacological effects in mice

Abstract: sleeping time by 1.8 to 8.0 times as compared with the control solution with 1% Tween 80-saline. The ED 50 values (mg/kg, i.v.) of 9α-OH-HHC and 8-OH-iso-HHC for the antinociceptive effect were 14.1 and 39.4, respectively. The present study demonstrated that CBD can be converted to ∆ 9 -THC and its related cannabinoids, 9α-OH-HHC and 8-OH-iso-HHC, in artifi cial gastric juice, and that these HHCs show ∆ 9 -THC-like effects in mice, although their pharmacological effects were less potent than those of ∆ 9 -THC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 26 publications
2
58
0
1
Order By: Relevance
“…27,35-39 Furthermore, we have reported that CBD can be converted into 9 -THC in acidic conditions that are mimicked by stomach acid. 40 In acidic conditions, 9 -THC can be isomerized to 8 -THC. 41 If this is the case with 9 -THC-11-oic acid, the metabolic fate and action might be modulated by its administration route (i.e., oral vs. intravenous administration).…”
Section: Resultsmentioning
confidence: 99%
“…27,35-39 Furthermore, we have reported that CBD can be converted into 9 -THC in acidic conditions that are mimicked by stomach acid. 40 In acidic conditions, 9 -THC can be isomerized to 8 -THC. 41 If this is the case with 9 -THC-11-oic acid, the metabolic fate and action might be modulated by its administration route (i.e., oral vs. intravenous administration).…”
Section: Resultsmentioning
confidence: 99%
“…9,10‐α‐epoxyhexahydrocannabinol (9,10‐α‐EHHC) was found to be formed from Δ 9 ‐tetrahydrocannabinol (Δ 9 ‐THC) 48. Further, pharmacological effects of 9,10‐α‐EHHC in mice, were compared with those of Δ 9 ‐THC in catalepsy, hypothermia, pentobarbital‐induced sleep prolongation and anticonvulsant activity against pentylenetetrazol (PTZ) 48, 49. 9,10‐α‐EHHC was approximately as equipotent as THC in the pharmacological indexes except for catalepsy.…”
Section: Materials Methods and Techniquesmentioning
confidence: 99%
“…The mixture was extracted with 4 ml of ethyl acetate after addition of 0.5 ml of 1 M KH 2 PO 4 , and 5 0 -nor-D 8 -THC-4 0 -oic acid methyl ester (0.5 lg) as an internal standard. After evaporation of the organic solvent, the residue was trimethylsilylated as described previously [14][15][16] and subjected to gas chromatography-mass spectrometry (GC-MS) under the following conditions: instrument, Shimadzu GCMS-QP2010 (Shimadzu, Kyoto, Japan); column, DB-1 (0.25 mm 9 30 m, film thickness 0.25 lm, Agilent, Santa Clara, CA, USA); column temperatures, 50°C (1-min hold), 25°C/min (6 min), 10°C/min (10 min), and 300°C (5-min hold); ion source temperature, 250°C; interface temperature 280°C; ionization energy, 70 eV; emission current, 60 lA; carrier gas, He at flow rate of 2.04 ml/min. Under these conditions, the retention times of the trimethylsilyl (TMS) derivatives of the THC metabolites were: 4 0 -hydroxy-D 8 -THC, 15.14 min; 5 0 -hydroxy-D 8 -THC, 15.76 min; 4 0 -hydroxy-D 9 -THC, 15.21 min; 5 0 -hydroxy-D 9 -THC, 15.84 min.…”
Section: Methodsmentioning
confidence: 99%
“…These retention times were very similar to those of the authentic standards for 4 0 -and 5 0 -hydroxy metabolites of THCs.In GC-MS analyses, all of the metabolites showed molecular ions at m/z 474, and a fragment ion at m/z 391 that is a typical diagnostic ion of pentyl side chain hydroxylated metabolites of THCs(Fig. 2)[15,16]; the mass spectra of these metabolites were almost identical with those of synthetic standards or…”
mentioning
confidence: 89%